Efectos de la variabilidad climática con diferentes densidades de siembra en el cultivo de arroz (oryza sativa) variedad capirona en bosque seco tropical en el distrito de Cacatachi región San Martín - Chinchay Rubio, Santos Edin (2007)
The present Word was Developer among on august 2005 until on January 2006, with to evaluating those effects of the climatic variability y with different sowings densities in the crop of rice (oryza sativa)''this experiment was carried in the found 2A of the national university of San Martín located in the district of Cacatachi, province and department of San Martín, located geographically to 6º 22'south latitude, 76<'12'1ongitude west, with an altitude of 330 m.s.n.m.m, the statistical design was used of (OBCR)with 04 treatments and 03 repetitions. The research work consisted on carrying out the following activities: preparation of the bed seedbed sprinkle from the seed to reason of 80 kg/ha, with sowing Separations of: T1=30 x20cm, T2=30x25cm, T3=30x30cm y T4= normal transplant. Control pre result underbrush take a out weed, intermittent waterings and periodic floods were used in required moments. it was fertilized with a dose of 140 - 80 – 46 of NPK. They also registered the data of temperature, precipitation and humidity of the atmosphere, as well as the data of temperature and humidity of the floor were determined. The results suggest that the biggest yield grain (kg/) obtained:T3 with 7763,78 kg/ha. Following of T4 with 7323,56 kg/ha; T2 with 7221,80 kg/ha and T1 with 7179,50 kg/ha, this ri:ght to 14% of humidity.